2020
DOI: 10.3389/fnagi.2020.00102
|View full text |Cite
|
Sign up to set email alerts
|

Insula and Amygdala Atrophy Are Associated With Functional Impairment in Subjects With Presbycusis

Abstract: Belkhiria et al. Neurobehavioral Impairment in Presbycusis that (i) the neuropsychiatric symptoms had a major effect on functional loss in subjects with presbycusis, (ii) cochlear dysfunction is relevant for the association between hearing loss and behavioral impairment, and (iii) atrophy of the insula and amygdala among other temporal areas are related with hearing loss and behavioral impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 86 publications
3
27
0
Order By: Relevance
“…DPOAE were measured at eight different frequencies per ear, between 707 and 3563 Hz. For subsequent analyses we counted the number of detected DPOAE, a value that considering both ears, goes from 0 to 16 (see [9,13] for more details on DPOAE analysis). ABR waveforms were averaged with alternating clicks presented at supra-thresholds levels (2000 repetitions, 80 dB nHL, bandpass 0.1-3 kHz, stimulus rate 21.1 Hz, EP25, Eclipse, Interacous-tics1).…”
Section: Auditory Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPOAE were measured at eight different frequencies per ear, between 707 and 3563 Hz. For subsequent analyses we counted the number of detected DPOAE, a value that considering both ears, goes from 0 to 16 (see [9,13] for more details on DPOAE analysis). ABR waveforms were averaged with alternating clicks presented at supra-thresholds levels (2000 repetitions, 80 dB nHL, bandpass 0.1-3 kHz, stimulus rate 21.1 Hz, EP25, Eclipse, Interacous-tics1).…”
Section: Auditory Evaluationsmentioning
confidence: 99%
“…Presbycusis is also associated with executive dysfunction [8,9] and with brain atrophy in the temporal lobe [10,11]. Moreover, recent studies in presbycusis have shown cortical atrophy in regions beyond the auditory cortex, including the cingulate cortex and parietal regions [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They did not have any diagnosed neurological diseases, and were not using hearing aids at enrollment in the study. More details about the inclusion and exclusion criteria can be found in our previous works 25,26 . The study was approved by the Ethical and Scientific Committee of the Clinical Hospital of the University of Chile (HCUCH), permission number OAIC 752/15.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that our study explores audition, and FER we looked for the main cortical and subcortical brain areas responsible of these functions in the literature: (1) temporal cortex, 38 (2) cingulate 26,39 (3) amygdala, 17 and (4) insula 40–42 . Other regions such as hippocampus, thalamus, lingual, fusiform gyrus, and accumbens area were also included because of their early damage in Alzheimer's disease 43 …”
Section: Methodsmentioning
confidence: 99%
“…Currently, these are powerful tools to objectively assess the degree of hearing loss, cochlear function, and auditory nerve–auditory pathway in patients. A limited number of studies have correlated OAE (Belkhiria et al, 2019 , 2020 ) and ABR (Delano et al, 2020 ) with magnetic resonance imaging (MRI) which is the most commonly used objective measurement tool of cognitive function. Furthermore, electroencephalogram (EEG) technology has become another potential tool to measure cognitive function.…”
Section: Cognitive Screening Tools Overviewmentioning
confidence: 99%